Elephantiasis and nodular scabies coinfection: a rare case report - Armiyanti, Yunita; Shodikin, Muhammad Ali; Tohari, Achmad Ilham (Indonesian Pediatric Society, 2025)
Indonesia is a tropical country and home to many infectious diseases. Two of them are filariasis and scabies. The coinfection of filarial infection and scabies may cause severe morbidity for the patient, especially children. There has been no reported coinfection or management between these two diseases. An 11-year-old boy was brought to the pediatrics division of Dr. Soebandi Hospital with diffuse enlargement of the left lower extremity and scrotum, along with non-pitting edema, itching, and nodular skin lesions all over the body. It is important to consider holistic approaches to prevent further morbidity and disability.